Psychometric Properties of the Czech Version of the Vanderbilt ADHD Diagnostic Parent Rating Scale - Sebalo Vňuková, Martina; Sebalo, Ivan; Anders, Martin; Ptáček, Radek; Surman, Craig (Journal of attention disorders, 2023)
This study examined the psychometric properties of the Czech translation of the Vanderbilt ADHD Diagnostic Parent Rating Scale (VADPRS), a tool used to assess ADHD symptoms. Data was collected online from parents of school-aged children and included questions related to their child's diagnosis or treatment. The results showed that while relying on professional judgment improved specificity and positive predictive value, it decreased negative predictive value. These findings indicate that the VADPRS scale is more accurate in identifying individuals with ADHD when professionals provide the diagnosis, but fewer true negatives are found. This is the first study attempting to describe the psychometric properties of this tool in the Czech Republic and assess its use as an additional tool for ADHD diagnosis. It is recommended that structured clinical interviews be used to increase the accuracy of ADHD diagnosis.
Keywords: Psychometrics; hyperkinetická porucha; Child; parent rating; Attention Deficit Disorder with Hyperactivity; rodiče; lidé; Česká republika; Humans; psychometrie; dítě; ADHD; Parents; Reproducibility of Results; reprodukovatelnost výsledků; child ADHD; Czech Republic